EHPS UN Grant Report: Conducting a science communication project on health psychology topics on Instagram - Alice Elena Seffen; Rebecca Blase; Liesemarie Albers (European Health Psychologist, 2026)
Science communication is essential for increasing the societal impact of health psychology research, yet translating academic findings into accessible and engaging content remains challenging. This report describes the planning, implementation, and evaluation of an EHPS UN–funded science communication project conducted on Instagram in collaboration with the In-Mind magazine. The project aimed to enhance public understanding of health psychology by communicating research on sleep, eating behavior, and health and risk communication through theme weeks on Instagram complemented by peer-reviewed In-Mind blog posts. Content creation followed evidence-based principles of effective science communication and incorporated interactive elements to foster engagement. Over a three-week implementation phase, the project reached 19,772 accounts, generated 714 content interactions, and attracted 453 new followers, indicating substantial increases compared to the previous month. Additionally, we received positive user feedback. Three key lessons emerged from this project: set realistic goals that align with available resources, adapt content to platform-specificcharacteristics, and gather feedback from both experts and lay audiences. Overall, the project demonstrates the feasibility and impact of strategic, collaboration-based science communication in health psychology.